FROM SYMPTOMS TO SOLUTIONS: THE BIOCHEMICAL POWER OF LIFESTYLE IN PCOS - Aleksandra Maciejczyk; Katarzyna Krupa; Natalia Kraciuk; Alicja Bury; Karol Bartecki; Julia Błoniecka; Małgorzata Piekarska-Kasperska; Anna Daniel (International Journal of Innovative Technologies in Social Science, 2025)
Background: Polycystic ovary syndrome (PCOS) is a complex endocrine and metabolic disorder affecting up to 20% of women of reproductive age. Characterized by hyperandrogenism, ovulatory dysfunction, and polycystic ovarian morphology, PCOS is frequently accompanied by insulin resistance, chronic inflammation, and an increased risk of cardiometabolic diseases. Objective: This narrative review synthesizes current evidence on the role of dietary patterns, specific nutrients, and physical activity in the management of PCOS. The aim is to highlight lifestyle strategies that target the underlying metabolic and hormonal disturbances and to support their use as first-line therapeutic interventions. Methods: A structured literature search was conducted in PubMed, Scopus, and Web of Science (2010–2025) using terms related to PCOS, nutrition, exercise, insulin resistance, and supplementation. Articles were selected based on relevance, methodological quality, and adherence to PRISMA 2020 guidelines. Results: Evidence supports the efficacy of low glycemic index, Mediterranean, and DASH diets in improving insulin sensitivity, reducing hyperandrogenism, and restoring menstrual regularity. Specific nutrients such as inositols, omega-3 fatty acids, and vitamin D show additional benefits, particularly in improving metabolic and reproductive outcomes. Physical activity—including aerobic, resistance, and high-intensity interval training—enhances insulin action, reduces visceral adiposity, and improves ovulatory function. Lifestyle interventions also lower long-term risks of type 2 diabetes and cardiovascular disease in PCOS. Conclusion: Diet and exercise are powerful, evidence-based tools in the management of PCOS. Integrating nutritional biochemistry and exercise physiology into clinical care offers a non-pharmacological, multifaceted approach that improves both short- and long-term outcomes.